Procesos administrativos en Barbershop JJ de la parroquia San Juan en el periodo 2022. - Justillo Márquez, Joseph Fernando (2023)
This research project focuses on analyzing the administrative processes and growth potential of Barbershop JJ. The Structural Analysis Method, which included structured interviews and a SWOT analysis, was employed to gain a comprehensive understanding of the current business situation. The interview with the manager revealed deficiencies in schedule management, lack of employee engagement and other problems in administrative processes. The SWOT analysis highlighted strengths such as qualified personnel and a strategic location, but also weaknesses such as administrative inefficiency and timeline. As a result, specific recommendations were made to improve the barbershop. These include establishing reliable opening hours, assigning working hours that suit the needs of employees, introducing new services, improving supply management, and training staff. The use of social networks for promotion and customer feedback is also suggested. This study provides a comprehensive overview of Barbershop JJ's challenges and opportunities, and offers concrete recommendations for achieving business growth and increased competitiveness.